Prevalence And Reasons For Missed Dental Appointments Among Patients Treated By Undergraduate Dental Students Of Universiti Sains Islam Malaysia - Nur Farah Insyirah Khairuddeen; Nur Haifa Najihah Ahmad Nazari; Aws Hashim Ali Al-Kadhim; Norashikin Amran; Nor Faharina Abdul Hamid; Ahmad Dzulfikar Samsuddin; Azlan Jaafar (IIUM Press, 2024)
Non-Indexed Publication